ŞILEA VILLAGE, A POSSIBLE FUTURE TOURISM VILLAGE (PANGEEA, 2025)
This paper is the structure of a comprehensive study of the natural conditions in the village of Şilea for the elaboration of a project for the development of the area. We have just mentioned a few features related to the geographical location of the area and the main natural features that constitute the main tourist potential of the village area.
Keywords: geographic location; isolated village; natural conditions; tourist potential